Seguridad y Salud Ocupacional y su Incidencia en los riesgos del personal del Relleno Sanitario de Curgua del GAD Municipal del cantón Guaranda, provincia Bolívar año 2019 - Gaibor González, Julissa Yolanda (2019)
Occupational safety and health research and its impact on the risks of Curgua landfill personnel from the municipal GAD of the canton Guaranda, Bolivar province, year 2019. Whose objective of this work was to design the occupational health and safety plan to mitigate the risks of staff; dedicated to the sweeping, collection, transport and final disposal of solid waste produced in the city. The study was of a descriptive and field type, using inductive, deductive, scientific and historical-logical methods; based on information-lifting techniques and tools such as the survey designed and validated with 19 questions, three of them demographic; the interview, one addressed to the director of municipal environmental management, another to the landfill manager and the observation developed at the study site. The sample consisted of the 44 workers who make up the entire object of study. The results yielded the following information: workers have generally been incapacitated by accidents at work represented by 33% (n=14); the personal protective elements they frequently use are gloves, mask, uniform or overall with reflective bands and safety footwear with the 50% (n=21), leaving aside the protection for ears, head and eyes. On the other hand, 33% (no. 14) of staff consider that "sometimes" protective equipment provides the required security. The most frequent injuries they have suffered are bumps and cuts with 14% (n = 6). 100% (no. 42) of the population surveyed manifests that they have no knowledge of the existence of an occupational health and safety plan. It was concluded in a general way that the development and implementation of the proposal will significantly reduce the risk of accidents and incidents in workers.